A Brief History of Theology: From the New Testament to Feminist Theology - Johnson D.; Johnston Derek (London New York Continuum International Publishing Group, 2008)
A fun, concise and attractive introduction to a fascinating and challenging subject. This is the ideal book for secondary school students and undergraduate students coming to theology for the first time, or indeed for anyone who just doesn't know where to start. The book examines key thinkers from the New Testament to Feminist Theology. It starts by considering some of the authors of New Testament writings and then focuses on representatives of the western tradition of theological speculation. Nearly half the work concentrates on 20th century thinkers and problems. It puts them in their historical, social and cultural settings, emphasizing that theology is as much a reflection on the world we live in as it is on God. Technical terms are explained in simple language throughout the text. This makes the book an ideal reference tool for a clear first overview of theology.
Keywords: 27 (NhRISTIQNSTWOs